2015
DOI: 10.1093/humrep/dev117
|View full text |Cite
|
Sign up to set email alerts
|

NEDD8-mediated neddylation is required for human endometrial stromal proliferation and decidualization

Abstract: This work was supported in parts by the National Basic Research Program of China (2011CB944400 to H.W.) and the National Natural Science Foundation (81130009, 81330017 to H.W., 81170575 to S.Q. and 31471106 to S.Z.). The author declares that there is no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Collectively, the screens revealed several expected results, such as FKBP4 (36,44) and NEDD8 (45), showing up as hypoinduced hits (required for decidualization) in the siRNA screen, and prostaglandins (46), showing up as hits in the small-molecule screen (enhance decidualization when added exogenously). While Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Collectively, the screens revealed several expected results, such as FKBP4 (36,44) and NEDD8 (45), showing up as hypoinduced hits (required for decidualization) in the siRNA screen, and prostaglandins (46), showing up as hits in the small-molecule screen (enhance decidualization when added exogenously). While Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The most significant new eQTLs detected include eQTLs for NEDD8, RPS26, SNHG17, SNHG 5 and WARS2 . NEDD8 (neural precursor cell expressed, developmentally down-regulated 8) is a ubiquitin-like protein that targets the ubiquitin E3 ligase family 50 and may be important in regulating normal endometrial function 51 . One study found NEDD8 was expressed in luminal epithelium, glandular epithelium and the stromal cells during the menstrual cycle and that, when inhibited, it significantly decreased proliferation in human endometrial stromal cell lines (HESC) and disrupted decidual transformation 51 .…”
Section: Discussionmentioning
confidence: 99%
“…2). Indeed, cellular senescence in human endometrial stromal cells is accompanied by impaired decidualization as a consequence of inhibiting neddylation (Liao et al 2015) or suppressing the cAMP mediator, Rap guanine nucleotide exchange factor 3 (RAPGEF3) (Kusama et al 2014), resulting in a phenotype reminiscent of that observed with advanced age. In mice, persistently high levels of senescent cells in uteri by tissue-specific deletion of the tumor protein p53 (Trp53) gene in progesterone receptor-expressing cells also reduced decidual growth without altering the number of implantation sites (Hirota et al 2010).…”
Section: Cellular Senescence and Uterine Agingmentioning
confidence: 99%